A potentially endangered new species of the genus Rowlandius (Arachnida: Schizomida: Hubbardiidae) from Northeastern Brazil - Silva, Iara Siqueira Santos; Santos, Adalberto J.; Carvalho, Leonardo Sousa (Zootaxa, 2024)
A new species of schizomid, Rowlandius ufpi sp. nov., is described based on individuals collected in gallery and riverine forests in a Cerrado-Caatinga ecotone in northeastern Brazil. Rowlandius ufpi sp. nov. is the sixth species of the genus found in Brazil and raises to 62 the number of described species of genus Rowlandius. This is also the first epigean species of Rowlandius inhabiting a Brazilian dry forest leaf litter. Males of Rowlandius ufpi sp. nov. can be easily distinguished from other conspecifics by the presence of three depressions in the dorsal region of the flagellum, with the posteromedian depression located in the posterior third part of the dorsal surface. The females of Rowlandius ufpi sp. nov. are recognized by the sub-square shaped spermathecae with short median lobes.